Inflammation-Modulating Biomedical Interventions for Diabetic Wound Healing: An Overview of Preclinical and Clinical Studies - Nouf N. Mahmoud (9133074) (2024)
A diabetic wound exemplifies the challenge of chronic, nonhealing wounds. Elevated blood sugar levels in diabetes profoundly disrupt macrophage function, impairing crucial activities such as phagocytosis, immune response, cell migration, and blood vessel formation, all essential for effective wound healing. Moreover, the persistent presence of pro-inflammatory cytokines and reactive oxygen species, coupled with a decrease in anti-inflammatory factors, exacerbates the delay in wound healing associated with diabetes. This review emphasizes the dysfunctional inflammatory responses underlying diabetic wounds and explores preclinical studies of inflammation-modulating bioactives and biomaterials that show promise in expediting diabetic wound healing. Additionally, this review provides an overview of selected clinical studies employing biomaterials and bioactive molecules, shedding light on the gap between extensive preclinical research and limited clinical studies in this field. Other Information Published in: ACS Omega License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1021/acsomega.4c02251